2016
DOI: 10.1016/j.ejphar.2016.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated Alpha-Alumina nanoparticle with vasoactive intestinal peptide as a Nano-drug in treatment of allergic asthma in mice

Abstract: Conjugated Alpha-Alumina nanoparticle with vasoactive intestinal peptide as a Nano-drug in treatment of allergic asthma in mice, European Journal of Pharmacology, http://dx.doi.org/10.1016Pharmacology, http://dx.doi.org/10. /j.ejphar.2016 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting galley proof before it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 43 publications
2
47
0
Order By: Relevance
“…Inhalation of VIP analogue Ro 25–1553 (a selective VPAC-2 receptor agonist) leads to a rapid bronchodilatory effect in asthmatic patients without any side effects [149]. Additionally, conjugated alpha-alumina nanoparticle with VIP has been proposed as an effective nano-drug for the treatment of asthma [150]. Additionally, induced expression of VIP and VIP associated receptors were reported in patients with atopic dermatitis [20, 129], allergic rhinitis [116] and EoE [63], suggesting the use of stable VIP antagonists or specific VIP receptors antagonist may be the logical approach for improving these inflammatory diseases.…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…Inhalation of VIP analogue Ro 25–1553 (a selective VPAC-2 receptor agonist) leads to a rapid bronchodilatory effect in asthmatic patients without any side effects [149]. Additionally, conjugated alpha-alumina nanoparticle with VIP has been proposed as an effective nano-drug for the treatment of asthma [150]. Additionally, induced expression of VIP and VIP associated receptors were reported in patients with atopic dermatitis [20, 129], allergic rhinitis [116] and EoE [63], suggesting the use of stable VIP antagonists or specific VIP receptors antagonist may be the logical approach for improving these inflammatory diseases.…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…Athari SS, Pourpak Z, Folkerts G, Garssen J, Moin M, et al (2016) Conjugated Alpha-Alumina nanoparticle with vasoactive intestinal peptide as a Nano-drug in treatment of allergic asthma in mice. Eur…”
Section: Referencesmentioning
confidence: 99%
“…The asthma physiological hallmarks are air flow limitation and airway hyper responsiveness to broncho constrictor stimuli. The asthma standard therapy is potent antiinflammatory glucocorticoids and bronchodilation agents [1,2]. It is a chronic disease associated with immune system-biased inflammation.…”
Section: Opinionmentioning
confidence: 99%
“…Although the coupling of peptides to alumina nanoparticles seems to represent an excellent advantage in materials used as medical devices, little attention has been given to these promising nanobiomaterials. It was only recently shown that a peptide-alumina nanoparticle conjugate can be highly effective for the treatment of some biological conditions, such as allergic asthma in rats [14]. Very recently, our team proved the antimicrobial potential of nanofibrous alumina covalently bound to the antimicrobial peptide BP100 in assays against Escherichia coli and Salmonella typhimurium strains [15].…”
Section: Introductionmentioning
confidence: 96%